DAMPAK BUDAYA ORGANISASI, BEBAN KERJA, DAN KOMPENSASI TERHADAP TURNOVER INTENTION DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA UPTD PUSKESMAS PRAJEKAN BONDOWOSO - Makrufah, Inayatul; Hamdun, Edy Kusnadi; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2024)
Puskesmas is one of the most important health facilities that carries out the task of providing health services to the entire community. The function of the puskesmas is as a health center for health development in its area. The purpose of this study was to analyze and test the impact of organizational culture, workload and compensation on turnover intention with work motivation as an intervening variable at the Regional Technical Implementation Unit (UPTD) Prajekan Bondowoso Public Health Center. The population in this study were all Non ASN employees at Regional Technical Implementation Unit (UPTD) Prajekan Bondowoso Public Health Center with a population of 36 employees with sampling using saturated sampling techniques which means that it is taken as a whole. The analysis in this study used the help of the Smart PLS 3.0 application. The results of hypothesis testing in direct influence using the Smart PLS 3. 0, shows that organizational culture has a significant positive effect on work motivation, workload has a positive insignificant effect on work motivation, compensation has a significant positive effect on work motivation, organizational culture has a positive insignificant effect on turnover intention, workload has a positive insignificant effect on turnover intention, compensation has a positive insignificant effect on turnover intention, work motivation has a significant positive effect on turnover intention, organizational culture has a positive insignificant effect on turnover intention through work motivation, workload has a positive insignificant effect on turnover intention through work motivation, and compensation has a positive insignificant effect on turnover intention through work motivation.